Drug trafficking, cattle ranching and Land use and Land cover change in Guatemala's Maya Biosphere Reserve. (June 2020) - Devine, Jennifer A.; Currit, Nathan; Reygadas, Yunuen; Liller, Louise I.; Allen, Gabrielle
Abstract: Drug trafficking organizations are driving deforestation in Guatemala's Maya Biosphere Reserve. Drug traffickers deforest the protected area in order to illegally ranch cattle, which serves as a mechanism of money laundering, drug smuggling, and territory control. Journalists and ethnographers have analyzed "narco-cattle ranching" activities in the reserve and resulting "narco-deforestation, " yet land use change scientists have yet to quantify the contribution of illegal cattle ranching to forest loss. This article uses remote sensing and GIS analysis to distinguish the relative contribution of cattle ranching, farming, and land speculation to reserve deforestation and other forms of land use and land cover change. We also use ethnographic methods to provide evidentiary links between illegal cattle ranching and drug trafficking activities that suggest a large part, but not all, of illegal cattle ranching is narco-capitalized. Our research finds that illegal cattle ranching is responsible for the majority of reserve deforestation, ranging from 59 to 87% of photographs on deforested lands in three sampled areas. We also found illegal cattle ranching activities are the highest in the reserve's western national parks, which should be strictly protected from land use change. Contrary to popular debate, these findings suggest drug traffickers in the context of the US-led War on Drugs are to blame for forest loss, not subsistence farmers illegally living in the reserve.